LEARNING STYLES AND STRATEGIES IN TEACHING ENGLISH - Ernazarova Shaira Dalavaevna (Galaxy International Interdisciplinary Research Journal, 2024)
This article discusses the variability of styles of teaching foreign languages, in particular, English. A detailed explanation is given of the differences in the learning styles of students, as well as the possibilities and ways of introducing best practices into the daily activities of the teacher, including the curriculum and the evaluation system.